The Effect of Folic Acid Administration of Some Physiological Parameters in Normal Adult Male Rabbits - Mohammed Ali, Sabreen Majeed (The Iraqi Journal of Veterinary Medicine, 2012)
This study was conducted to find out the effect of folic acid at different doses (5 g and 10g/animal daily) on blood parameters in adult male rabbits. The animals were divided into 3 equal groups each group contained five animals. One of them as control and other as treated groups T1 and T2. The experiment lasted four weeks. GroupT1 got folic acid at dose 5 g/daily/animal and GT2 10g/animal. To study the hematological parameters such as [total red blood cell (RBC), total white blood cell (WBC), packed cell volume PCV, hemoglobin concentration (Hb) and using serum to detect total serum protein. The folic acid was causing significant increasing in most of these parameters due to the stimulating effect of it and anti-oxidant properties that protect the cell membrane from free radical. Therefore, the administration of folic acid is useful especially for children, pregnant women and aging people.